Instability mechanism and coupling support technology of full section strong convergence roadway with a depth of 1350 m. (September 2022) - Zhan, Qinjian; Muhammad Shahani, Niaz; Zheng, Xigui; Xue, Zhicheng; He, Yongyi
Highlights: Long-term strong convergence is the deformation feature of deep soft rock roadway. Larger floor heave is the objective law of deep soft rock roadway convergence. Instability process of roadway is the macroscopic embodiment of rock deterioration. High resistance and yield are inherent requirements of deep soft rock roadway support. Organic combination of components is an effective way to improve the support efficiency. Abstract: The nonlinear stability control of surrounding rock with large deformation is the key issue in realizing rapid excavation of deep soft rock roadway. Combined with various research methods, this paper deeply analyzes the characteristics of instability. Through the modified Drucker-Praeger criterion, the mechanism of roadway instability under the coupling actions of multiple factors is studied, and the control strategy of deep soft rock roadway is given. On this basis, the combined support scheme is optimized and verified by simulation, test and field application. The results show that: (1) Long aging, strong rheology and full section are the basic characteristics of deep soft rock roadway convergence. High resistance and yield are the inherent requirements of nonlinear large deformation roadway support. (2) The asymmetric support of roof and floor violates the objective law that the floor heave of deep soft rock roadway is larger. (3) Roadway instability is the result of comprehensive action of internal and external factors, which reflects the gradual deterioration process of the rock mass. The purpose of the support is to effectively improve the bearing capacity of the surrounding rock and avoid this process. (4) It is an effective measure to improve the support efficiency and an important way to realize the stability control of nonlinear large deformation roadway by combine the parts organically and coordinate their bearing performance.